EFFICIENCY IN ENTREPRENEURIAL ACTIVITY AND ITS DETERMINANTS - Raximov Shuxratdjon Shukurullayevich (European Science Publishing, 2024)
Entrepreneurship's pivotal role in economic growth and innovation is emphasized in Uzbekistan, where economic reforms are cultivating a robust landscape for small businesses. Regional dynamics, aligned with governmental insights and market mechanisms, foster entrepreneurship's development, echoing the nation's strategic goals. Successful initiatives in the Samarkand region highlight the symbiosis of internal growth drivers and international investments, shaping a promising entrepreneurial environment for sustained economic prosperity.
Keywords: Entrepreneurial activity, innovation, economic expansion, industrial development, small businesses, private entrepreneurship, regional characteristics, local government insights, economic reforms, economic and legal foundations, free economic activity.